2018
DOI: 10.1097/jpo.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with Unilateral Transtibial Amputation and Lower Activity Levels Walk More Quickly when Using a Hydraulically Articulating Versus Rigidly Attached Prosthetic Ankle-Foot Device

Abstract: Introduction Prosthetic ankle-foot devices incorporating a hydraulic articulation between the pylon and prosthetic foot have been shown to be beneficial to the gait of more active individuals with unilateral transtibial amputation (UTA). However, the functional benefits of using hydraulic ankle-foot devices to less active individuals with UTA are yet to be determined. The aim of the current study was to investigate the effects on gait performance of using a non-ESR foot with a hydraulic attachment, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, other approaches have been used to characterize the biomechanical function of prosthetic feet. In terms of kinematics, shank rotational velocity relative to a global horizontal axis 14 and center of pressure displacement and velocity 15 may provide information regarding the concept of progression during stance. From a kinetic perspective, methods that do not necessitate the definition of an ankle joint center to calculate ankle-foot complex power may be favorable.…”
Section: Discussionmentioning
confidence: 99%
“…However, other approaches have been used to characterize the biomechanical function of prosthetic feet. In terms of kinematics, shank rotational velocity relative to a global horizontal axis 14 and center of pressure displacement and velocity 15 may provide information regarding the concept of progression during stance. From a kinetic perspective, methods that do not necessitate the definition of an ankle joint center to calculate ankle-foot complex power may be favorable.…”
Section: Discussionmentioning
confidence: 99%
“…0:4 has been described as a 'medium' effect size 24 and past prosthetic research has defined this as being a clinically meaningful difference. 22,25 The statistical analyses were applied to comparisons between MI sup for MPF-on and MPF-off conditions, and only within walking conditions (e.g. MPF-on downhill vs. MPF-off downhill).…”
Section: Discussionmentioning
confidence: 99%
“…This can improve ground clearance and secure the biological knee, which is important for falls prevention. 9 Previous laboratory-based studies reported that a self-aligning ankle-foot reduced residuum-socket interface pressures in active users, 10 which could alleviate pain in the residuum longer term, improved walking 11 and enhanced quality of life 12 13 in users with lower activity levels.…”
Section: Introductionmentioning
confidence: 99%